BIPA-2 Reading-Writing E-Module Design Using Integrative Approach and Multicultural Based - Senjawati, Dessy; Idris, Nuny Sulistiany; Sundusiah, Suci (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The learning material development of Indonesian as a foreign language study (BIPA), especially electronic module of BIPA 2 is considered urgent since there are a lot of BIPA students who live abroad and cannot access Indonesian learning material easily. Thus, the aim of this study is to describe the need analysis and describe the design of the BIPA 2 Reading-Writing E-Module Using Integrative Approach and Multicultural Based. This research used ADDIE method (Analysis, Design, Development, Implentation, Evaluation). Specifically, on this research, the researcher explains the need analysis of BIPA 2 students and teachers regarding the needs for BIPA 2 E-Module. Moreover, on this research, the researcher also describes the design steps of BIPA 2 E-Module. The participants of this study were 4 BIPA 2 teachers and 4 BIPA 2 students from different institutions. The result of this research was that there were needs from teachers and students for the development of BIPA 2 E-Module. Then, the data of the need analysis was analyzed to design the product. The design of the product is essential in order to facilitate both students and teachers in teaching and learning Indonesian, to improve the students’ skills in reading and writing and to support BIPA students all over the world to study Indonesian since the product will be available to be downloaded on the internet.